Inflammatory Bowel Disease: Changing Associations to Mechanisms. Issue 9 (September 2016) - Click, Benjamin; Whitcomb, David C
Abstract : N/A: Managing the health of individual patients suffering from complex disorders is a challenge and is costly. Inflammatory bowel disease (IBD) is a prototypic complex disorder of the small and large intestines. Susceptibility is complex, severity is variable, and response to treatment is unpredictable. Di Narzo et al. ( Clin Transl Gastroenterol 7: e177; doi:10.1038/ctg.2016.34) bring diverse teams of physicians and scientists together to break down the mechanisms of IBD by linking pathogenic genetic variants with altered gene expression in specific cell types causing IBD. Framing new findings in the context of other complex diseases provides a roadmap for predictive medicine.